A202 DYSREGULATED ENDOPLASMIC RETICULUM STRESS PATHWAYS IN COLON-DERIVED ENTEROIDS FROM INFLAMMATORY BOWEL DISEASE PATIENTS DRIVE DC MATURATION LEADING TO A PRO-INFLAMMATORY PHENOTYPE. (26th February 2020) - Rees, W D; Stahl, M; Jacobson, K; Bressler, B; Sly, L M; Vallance, B; Steiner, T
Abstract: Background: Intestinal epithelial cells (IECs) rely on danger signals such as adenosine triphosphate (ATP) and endoplasmic reticulum (ER) stress to form an appropriate, coordinated immune response. Moreover, ER stress in IECs contributes to the pathogenesis of inflammatory bowel disease (IBD), and an increase in extracellular ATP concentrations is a risk factor for Crohn's disease (CD). Aims: We hypothesized that cells exposed to ER stress or ATP modulate innate immune responses, creating a pro-inflammatory environment that drives dendritic cell (DC) maturation. Methods: Caco-2 cells and human colon-derived enteroid monolayers were exposed to ATP or the ER stress inducer thapsigargin, stimulated with E. coli FliC flagellin, and ER stress markers CHOP, GRP78, and XBP1 s/u were measured via qPCR and western blot, and cytokine release was measured by ELISA. Next, monocyte-derived dendritic cells (moDCs) were cultured in Caco-2 or enteroid conditioned supernatants and their activation status measured via flow cytometry, and cytokine analysis was performed using Luminex platform. We also assessed ER stress markers, TLR5 expression, and cytokine expression differences between IBD and healthy controls (HC). Results: We found that ER stress amplified FliC-induced IL-8 and decreased CCL20 in Caco-2 cells. Moreover, in IBD subjects, we found an increase FliC-induced IL-8 response, and decreased TNFa and CCL20. moDCs cultured with conditioned media from Caco-2 or enteroid monolayers showed a proinflammatroy phenotype, with an increase in CD80, CD86, MHCII, and a decrease in CD103. Moreover, moDCs cultured in stressed Caco-2 supernatants increased release of IL-6, TNFa, and IL-12p70, and decreased IL-10, suggesting potential to induce inflammatory Th1 and/or Th17 cells.. DC activation correlated with the amount of FliC-induced IL-8. Interestingly, there were distinct differences in cytokine expression and basal ER stress between IBD and HC enteroid monolayers, suggesting a dysregulated ER stress pathway in IBD-derived enteroids. Conclusions: ER stress in Caco-2 cells and colon-derived enteroid monolayers enhances FliC-induced TLR5 responses, leading to a pro-inflammatory environment that drives DC maturation, which may link epithelial ER stress and immune cell activation in IBD. Furthermore, the cytokine and ER stress pathway differences between IBD and HC-derived enteroids suggests that prolonged periods of stress in IBD patients may rewire the IEC stem cell compartment, further perpetuating inflammation and disease. Funding Agencies: CCC, CIHR